Sagittal Knee Alignment Is Associated with Reduced Knee Flexion Range of Motion in Asymptomatic Elderly: A Cross-Sectional Study - Mustamsir, Edi; Putra, Domy Pradana; Aji, Aulia Pandu; Firladi, Haidar Abror; Auzan, Asyrafly; Sasongko, Armabar Dwipantara; Tegar, Bintang Taqwa Nan (Fakultas Kedokteran Universitas Brawijaya, 2026)
Knee alignment affects lower limb biomechanics and functional knee movement. However, the relationship between knee alignment and knee flexion range of motion (ROM) in healthy populations, particularly across different age groups, remains unclear. To compare coronal and sagittal knee alignment and knee flexion ROM between healthy young adults and elderly individuals, and to examine the association between knee alignment and knee flexion ROM using clinical goniometric assessment. This cross-sectional study included 64 healthy participants (32 young adults aged 20–24 years and 32 elderly individuals aged ≥60 years). Coronal and sagittal knee alignment and active knee flexion ROM were measured using a goniometer. Group differences were analyzed using independent t-tests and Chi-square tests, and associations between alignment categories and knee flexion ROM were assessed using the Kruskal-Wallis test. Elderly participants showed a higher prevalence of coronal varus alignment and sagittal flexion contracture compared with young adults. Mean knee flexion range of motion was significantly lower in elderly participants than in young adults (127.4±4.7° vs 137.6±4.4°, p<0.001). Coronal knee alignment was not significantly associated with knee flexion ROM in either young adults (p=0.056) or elderly participants (p=0.476). In contrast, sagittal knee alignment demonstrated a significant association with knee flexion ROM in elderly participants (p=0.017), whereas no significant association was observed in the young adult group (p=0.922). Sagittal knee alignment, rather than coronal alignment, correlates with reduced knee flexion range of motion in healthy elderly individuals. A straightforward clinical evaluation of sagittal alignment may assist in detecting early functional deterioration in ageing populations.